1997
DOI: 10.1007/s004310050634
|View full text |Cite
|
Sign up to set email alerts
|

Depressed natural killer cell activity due to decreased natural killer cell population in a vitamin E-deficient patient with Shwachman syndrome: reversible natural killer cell abnormality by α-tocopherol supplementation

Abstract: These results indicate that severe vitamin E deficiency caused impaired NK cell activity due to a decrease in the number of CD16+ CD56- NK cells and that this abnormality is reversible with alpha-Toc supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Many studies showed VE has a number of vital functions in plants, including the protection of chloroplasts from photooxidative damage (Munne-Bosch and Alegre 2002). Moreover, human nutritional studies have suggested that VE might play an important role in enhancing the function of the immune system (Adachi et al 1997), and the treatment or prevention of a number of serious diseases including cardiovascular disease (Pryor 2000) and cancer (Prasad et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed VE has a number of vital functions in plants, including the protection of chloroplasts from photooxidative damage (Munne-Bosch and Alegre 2002). Moreover, human nutritional studies have suggested that VE might play an important role in enhancing the function of the immune system (Adachi et al 1997), and the treatment or prevention of a number of serious diseases including cardiovascular disease (Pryor 2000) and cancer (Prasad et al 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Studies in human nutrition have shown that VE enhances immune system function (Adachi et al. ); prevents or retards the development of cardiovascular diseases and cancers (Stepan et al., ), inflammation (Watcharee et al., ) and ageing; and improves the histopathological changes induced by carbamazepine (Maheswari et al. ).…”
mentioning
confidence: 99%
“…Likewise, dietary supplementation with vitamin E (250 mg daily for 2 wk) can enhance NK cell cytolytic activity in advanced colorectal cancer cells obtained from patients [11]. Interestingly, the supplementation of vitamin E (administered at 100 mg/day for 8 wk) restored NK cell activity in a 16-month-old boy with Shwachman-Diamond syndrome which is classically associated with a persistent reduction in NK cytolytic activity [12]. Collectively, these findings suggest the involvement of dietary components in the regulation of NK cell tumoricidal activity.…”
Section: Dietary Influence On Nk Cell Propertiesmentioning
confidence: 98%